Strategi Pengembangan Wisata Air Terjun Oehala : Studi pada Kecamatan Mollo Selatan, Kabupaten Timor Tengah Selatan - Melkisedek Tanesab; Apriana H.J Fanggidae; Rolland E. Fanggidae; Markus Bunga (Jurnal Studi Perhotelan dan Pariwisata, 2023)
Purpose: This study aims to determine the Oehala Waterfall Tourism Development Strategy (South Mollo District, South Central Timor District). Data collection techniques Using questionnaires, interviews, and documentation. Methodology: The data analysis technique in this study used SWOT analysis, with the help of SPSS version 21 software. Result: The results showed that the results of internal factor analysis (IFAS) and external factor analysis (EFAS) obtained the following values: strength factor (2.96), weakness ( 0.98), opportunities (2.64) and threats (0.96). So that the coordinate points (1.68. 1.98) are obtained in quadrant I. This indicates that tourism in Oehala Waterfall faces various threats coming from outside, even so this sector still has internal strength. Through SWOT analysis obtained the SO (strength opportunities), WO (Weakness Opportunities), ST (Strength Threat), and WT (Weakness Threat) strategies, so as to maximize opportunities in order to prevent threats that could disrupt the Oehala Waterfall Tourism Development Strategy in order to carry out Development goals can be maximized